Pengaruh Sektor Keuangan Syariah Terhadap Pertumbuhan Ekonomi Indonesia - Khairunnisa; Syahrituah Siregar (PPJP ULM, 2026)
This study examines the effect of Islamic financial sector instruments on economic growth in Indonesia by focusing on three key variables: the distribution of Zakat, Infaq, and Sadaqah (ZIS) funds, the Indonesia Sharia Stock Index, and Islamic banking financing. The study employs a quantitative approach using monthly time series data from January 2022 to October 2024, resulting in 34 initial observations. The data were obtained from the Central Statistics Agency, the National Zakat Agency, Google Finance, and the Financial Services Authority. Multiple linear regression was applied to estimate the relationship between Islamic financial sector variables and Indonesia’s economic growth. The findings indicate that the three independent variables jointly have a significant effect on economic growth. Partially, the distribution of Zakat, Infaq, and Sadaqah funds has a positive and significant effect, while Islamic banking financing has a significant but negative effect. Meanwhile, the Indonesia Sharia Stock Index does not show a statistically significant effect on economic growth during the observed period. These findings suggest that the contribution of Islamic finance to economic growth is not uniform across instruments. Social finance appears to play a more direct role in supporting aggregate demand, whereas the effect of Islamic banking financing requires further attention, particularly regarding allocation efficiency, sectoral targeting, and transmission to the real economy.